Assessment of the quality of groundwater wells in the island Municipality of Panglao, Bohol, Philippines - Ma. Grace Sumaria (Annals of Tropical Research)
The study was conducted in the Municipality of Panglao, Bohol, Philippines to investigate water quality in 81 wells using parameters such as pH, dissolved oxygen (DO), electrical conductivity (EC), total dissolved solids (TDS), sodium chloride (NaCl), temperature, and nitrate-N. Spatial variation is analyzed through ArcGIS 10.6 and regression analyses.